Testing for Coliform and Escherichia Coli Bacteria in Bottled Water In Palembang City - Rika Puspita Sari MZ; Ananda Nawal Syahidah; Ade Vera Yani; Suyatno Suyatno; Dasir Dasir; Sukmawati Usman (Universitas Muhammadiyah Palembang, 2026)
Bottled Drinking Water (AMDK) is a drinking water product provided in packaging and comes from various sources such as mountain springs to groundwater. It is then processed by sterilization, packaged, and is safe to drink. Food safety in AMDK must meet physical and chemical, as well as microbiological requirements according to the Indonesian National Standard (SNI 3553:2015). This study aims to explore the safety of AMDK products by identifying the presence of coliform and e. coli. The method used is descriptive quantitative. A total of five commercial AMDK test samples with 600 mL Bottle packaging in Palembang City were analyzed microbiologically including coliform and e. coli tests with CCA media. The test results showed that three of the five samples were positive for coliform contamination and one of the five samples was positive for E. coli contamination. However, two of the five samples were found negative for coliform and E. coli.